La potencia y su incidencia en la agilidad motriz de los boxeadores pre-juveniles. - Aguas Alvarez, Andy Mateo (2025)
The present study, unique in its focus on evaluating the impact of power training on the motor agility of pre-youth boxers, was conducted with a sample of boxers from the city of Riobamba who belonged to the pre-youth category. An agility test, consisting of a series of obstacles that had to be completed in the shortest time possible, was used to measure agility. A training program combining specific exercises aimed at improving power was implemented over 12 weeks. The program consisted of three weekly sessions, each lasting 90 minutes. Before and after the intervention, the agility test was applied to assess progress. The results were analyzed using the paired Student’s T-test. The results showed significant improvements in the boxers' agility, with a notable reduction in circuit completion times. Additionally, power improvements were substantial, positively impacting the athletes' ability to perform quick and precise movements. In conclusion, the power training applied to pre-youth boxers improved both their motor agility and movement precision, demonstrating the effectiveness of this approach in optimizing the physical and technical performance of young athletes.